Molecular detection and assessment of the epidemiological risk factors associated with equine herpesvirus 2 and 5 in working equids in central Ethiopia. Issue 6 (5th September 2022) - Wondimagegnehu, Kifle; Leta, Samson; Amenu, Kebede; Negussie, Haileleul
Abstract: Background: Respiratory disease is the most common presenting complaint at veterinary clinics and a priority concern for equid owners and veterinary practitioners in Ethiopia. Objectives: This study aimed to report the molecular detection of EHV‐2 and EHV‐5 and to assess the risk factors associated with infection in working equids in central Ethiopia. Methods: Nasopharyngeal swabs were collected from 58 horses and donkeys to detect EHV‐2 and EHV‐5 using PCR targeting the conserved region of glycoprotein B (gB) genes. Results: From 58 equids, EHV‐5 and EHV‐2 were detected in 20 (34.5%) and 19 (32.8%) equids, respectively. Concurrent infection with EHV‐2 and EHV‐5 was found in 6 (10.3%) equids who exhibited respiratory clinical signs. EHV‐2 was detected in a significantly higher ( p = 0.002) proportion of horses (54.5%; n = 18) than donkeys (4%; n = 1). In contrast, EHV‐5 was detected in a significantly higher ( p = 0.004) proportion of donkeys (56%; n = 14) compared to horses (18.2% n = 6). EHV‐2‐positive equids were seven times more likely to display clinical signs of respiratory disease than EHV‐2‐negative equids (Odds ratio (OR) = 6.9; 95%CI: 1.72‐27.60). However, statistically significant ( p = 0.832) difference was not observed for EHV‐5. EHV‐2 was detected in a significantly higher ( p = 0.004) proportion of female (50%; n = 16) compared to male equids (11.5%; n = 3). Conclusions: This study revealed the molecular detection of EHV‐2 and EHV‐5 in horses and donkeys residing in central Ethiopia. The association between EHV‐2‐test‐positive equids and displaying of clinical signs of respiratory disease was observed, which suggests EHV‐2 involvement in the development of respiratory disease; however, it deserves further investigation. Abstract : This study revealed the molecular detection of EHV‐2 and EHV‐5 in horses and donkeys in central Ethiopia. We demonstrated that the association between EHV‐2‐test‐positive equids and displaying of clinical signs of respiratory disease, which suggests EHV‐2 involvement in the development of respiratory disease.